Feedback That Leads to Improvement in Student Essays: Testing the Hypothesis that “Where to Next” Feedback is Most Powerful - Hattie, John; Crivelli, Jill; Van Gompel, Kristin; West-Smith, Patti; Wike, Kathryn (Frontiers in Education, 2021)
Feedback is powerful but variable. This study investigates which forms of feedback are more predictive of improvement to students’ essays, using Turnitin Feedback Studio–a computer augmented system to capture teacher and computer-generated feedback comments. The study used a sample of 3,204 high school and university students who submitted their essays, received feedback comments, and then resubmitted for final grading. The major finding was the importance of “where to next” feedback which led to the greatest gains from the first to the final submission. There is support for the worthwhileness of computer moderated feedback systems that include both teacher- and computer-generated feedback.